Pemanfaatan Kababaji (Kalkulator Berat Badan Janin) Pada Ibu Hamil sebagai Kontrol Kesehatan Janin - Zata Ismah; Mhd Furqan (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2021)
To overcome the problem of low fetal weight (BBJR), then neonatal health problems can be resolved early. Recording, reporting and early intervention are necessary to avoid these losses. Including awareness of pregnant women in terms of fetal health status is an important key in the preventive paradigm. Therefore it is necessary to provide a light and simple application that pregnant women can use independently to find out whether their fetal weight status is normal or not. The activity of using this application is targeted at 164 pregnant women who have their pregnancy checked by midwives / obstetricians in Palembang City. The results of this activity are very helpful for mothers to know their fetal weight independently with the main display of the application which is very simple and easy to use; for shortcomings the operation of this application requires hardware in the form of a Personal Computer (PC). This tool will facilitate the data collection process for pregnant women with high risk, which in the future is expected to be integrated with the existing surveillance system in the health office